COLIBRI: A hovering flapping twin-wing robot. Issue 4 (December 2017) - Roshanbin, A; Altartouri, H; Karásek, M; Preumont, A
This paper describes the results of a six-year project aiming at designing and constructing a flapping twin-wing robot of the size of hummingbird ( Colibri in French) capable of hovering. Our prototype has a total mass of 22 g, a wing span of 21 cm and a flapping frequency of 22 Hz; it is actively stabilized in pitch and roll by changing the wing camber with a mechanism known as wing twist modulation. The proposed design of wing twist modulation effectively alters the mean lift vector with respect to the center of gravity by reorganization of the airflow. This mechanism is modulated by an onboard control board which calculates the corrective feedback control signals through a closed-loop PD controller in order to stabilize the robot. Currently, there is no control on the yaw axis which is passively stable, and the vertical position is controlled manually by tuning the flapping frequency. The paper describes the recent evolution of the various sub-systems: the wings, the flapping mechanism, the generation of control torques, the avionics and the PD control. The robot has demonstrated successful hovering flights with an on-board battery for the flight autonomy of 15–20 s.